Do clients with spinal cord injuries know what they need to know about pressure ulcers? A descriptive study on the knowledge, beliefs and practices about pressure ulcers - Visser, Adri Marica (Stellenbosch : Stellenbosch University, 2016)
Thesis (MHumanRehabSt)--Stellenbosch University, 2016.